Emotional Intelligence and Conflict Management Strategies among Junior and Senior Uniformed Personnel in Philippine National Police - Cuevas, Kamille Gretchen Z.; Pendon, Lerwin Aries T.; Rijon, Klyzia C.; Vibar, Jerome M.; Villa, Elizabeth Buena (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the emotional intelligence and conflict management strategies among junior and senior uniformed personnel of Philippine National Police. This study employed the use of descriptive comparative research design utilizing survey methodology. Research locale was limited Cavite. The respondents were the 50 junior uniformed personnel and 50 senior uniformed personnel in the locale of the study and were selected using random sampling technique. The research instrument in this study was a survey questionnaire adopted from Galman (2021). Data were analyzed using percentage, mean, rank order and One Way Analysis of Variance. The study reveals that senior uniformed personnel have higher emotional intelligence and conflict resolution skills compared to younger personnel. Senior personnel have a better understanding of their own emotions and others', and can better manage stress. They also employ more effective conflict resolution tactics. The study suggests that age and experience may influence emotional intelligence and conflict resolution. The study suggests that company culture can impact conflict management and emotional intelligence. It's crucial to tailor conflict management tactics to each age group and provide training to enhance emotional intelligence. Emphasizing these differences can help foster a more efficient professional environment among uniformed staff.